Exploring Gender Differences in Self- Efficacy and Academic Performance among College Students - Heber Dumanjug; Jennifer Serato; Maria Kristina Vicente; Jannah Panaguiton; Zari Shane Recto (EduLine: Journal of Education and Learning Innovation, 2024)
This study explored the relationship between self-efficacy and academic performance on gender and academic program differences among 204 undergraduate students at a university in Misamis Occidental. This study employed a descriptive-correlational method. The respondents were predominantly female with the majority enrolled in Social Work and Psychology. While they showed a strong belief in their academic abilities, this inconsistently translate into higher academic performance. Significant differences in self-efficacy were observed across academic programs, with Social Work students reporting the highest levels and Psychology students the lowest. However, gender insignificantly impact either self-efficacy or academic performance. This study suggests that self-efficacy must interact with other factors, such as motivation, learning strategies, and program-specific influences, instead of making it a direct predictor of academic success. Investigating the long-term impact of self-efficacy on academic outcomes, the role of external factors and their interaction with self-efficacy, and their contribution to a deeper understanding of its influence on academic outcomes must also be considered for further studies. Institutions should implement targeted interventions to enhance student self-efficacy and academic resilience as additional support for lower-performing programs for a more holistic approach to student development in higher education.